Analysis Between CBR, Rolling Resistance and Soils Bearing Capacity with Dump Truck Velocity in Mine Hauling Road Use Linear Regression Methods - Yazid Fanani (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2020)
The main effect of hauling using dump trucks are effected by haul road, machine condition, and weather. The purpose of this research to analyze the connection between CBR, rolling resistance and soils bearing capacity with dump truck velocity use linear regression methods by mathematical model approach. Dump truck velocity as dependent variable (Y). CBR, rolling resistance and soils bearing capacity as the independent variable (X). Based on this research, rolling resistance has a negative effect to dump truck velocity. Dump truck velocity decrease 0,13 – 0,14 km/h by 10 lbs increase of rolling resistance. CBR dan soils bearing capacity have a positive effect to dump truck velocity. Increase 5 % of CBR and 0,34 kg/cm2 soils bearing capacity can increase dump truck velocity 0,48 – 0,66 km/h. To increase dump truck velocity, the minimum CBR value on the haul road is 15 % and soils bearing capacity 6,79 kg/cm2 with a maximum rolling resistance value of 40 lbs.